Dampak Pandemi Covid-19 Terhadap Kondisi Makroekonomi Kabupaten/Kota di Provinsi Bengkulu - sibagariang, firma -; Putri, Novi Tri (Universitas Bengkulu, 2022)
This study aims to analyze the impact of the Covid-19 pandemic on the macroeconomic conditions of districts/cities in Bengkulu Province. This study uses a quantitative descriptive approach. This quantitative approach is used by researchers to measure changes in conditions by increasing and decreasing data for each macroeconomic indicator. This study uses secondary data from the Central Statistics Agency from 2019-2020. Based on the results of the study, district/city macroeconomic indicators were negatively and positively affected during the pandemic. Based on six macroeconomic indicators, it can be concluded that the area that was most negatively affected during the Covid-19 pandemic in 2020 was Bengkulu City, where 5 of the indicators experienced a decline with 3 of them the largest decline compared to other regions. The implementation of the Large-Scale Social Restrictions (LSSR) policy to prevent the spread has had an impact on economic activities which have an impact on decreasing economic growth, decreasing per capita income, increasing unemployment, increasing poverty, increasing the Gini ratio and increasing the human development index. Meanwhile, North Bengkulu Regency has a positive impact on 4 macroeconomic indicators, namely: an increase in the human development index, a decrease in unemployment, a decrease in poverty and a decrease in the Gini ratio. Keywords : Pandemic1, Impact2, Economic Growth3, Per Capita Income4, Unemployment5, Poverty6, Gini Ratio7, Human Development Index8